2005
DOI: 10.1007/s00280-005-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase gene polymorphisms: genomic predictors of clinical response to fluoropyrimidine-based chemotherapy?

Abstract: Fluorouracil (5-FU) is widely used in the treatment of colorectal cancer. Methylenetetrahydrofolate reductase (MTHFR) may play a central role in the action of 5-FU, an inhibitor of thymidylate synthase, by converting 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate. The aim of this study was to ascertain whether two polymorphisms in the MTHFR gene (677C>T and 1298 A>C) could be used as genomic predictors of clinical response to fluoropyrimidine-based chemotherapy (in combination with irinotecan or ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 16 publications
7
47
2
Order By: Relevance
“…So far, clinical studies including variants in TS 30-34 and MTHFR [35][36][37] have not shown univocal results. It is to be said that findings across clinical studies with TS and MTHFR polymorphisms in CRC patients are poorly comparable.…”
Section: Discussionmentioning
confidence: 99%
“…So far, clinical studies including variants in TS 30-34 and MTHFR [35][36][37] have not shown univocal results. It is to be said that findings across clinical studies with TS and MTHFR polymorphisms in CRC patients are poorly comparable.…”
Section: Discussionmentioning
confidence: 99%
“…First, indeed, from a simple blood sample taken before chemotherapy, physicians can be warned of a high risk of severe or even lifethreatening toxicity for a patient, that is relevant DPD and/or MTHFR variants regardless of the 5-FU regimens and the type of cancer. 23,29 Taking into account the wide use of 5-FU and other fluoropyrimidines, this is of major interest. In practice, in cases of a DPD deficiency, either 5-FU dose management based on a pharmacokinetic follow-up can be proposed after a reduced first dose of 5-FU or the switch to another drug, such as raltitrexed.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was clearly demonstrated both in experimental studies and in clinical settings. [18][19][20][21][22][23] The purpose of this study was to analyze the correlation between TS, DPD and MTHFR germinal polymorphisms on efficacy and toxicity of fluorouracil and leucovorin chemotherapy in patients with advanced CRC. Our objective was to provide a tool for physicians to determine before treatment patients at risk of 5-FU toxicity or resistance.…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the mutations do not bear prognostic value on their own, it has been suggested that the combination of wild-type MTHFR genotype (1298A or 677C) with the 3R/3R TS genotype shows significantly lower overall survival. 63 The clinical importance of the MMR status of tumors with regard to prognosis and response to adjuvant 5-FU chemotherapy has been increasingly studied the last few years. Patients diagnosed with stage II colorectal cancer, whose tumors were found to have unstable microsatellites (MMR deficient or MSI þ ), carry a better prognosis than do the microsatellite stable (MMR proficient or MSIÀ) ones.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%